2017
DOI: 10.1038/s41598-017-14681-6
|View full text |Cite
|
Sign up to set email alerts
|

The Phe362Tyr mutation conveying resistance to organophosphates occurs in high frequencies in salmon lice collected from wild salmon and trout

Abstract: The parasitic salmon louse, and its resistance to chemical delousing agents, represents one of the largest challenges to the salmon aquaculture industry. We genotyped lice sampled from wild salmon and sea trout throughout Norway with the recently identified Phe362Tyr mutation that conveys resistance to organophosphates. These results were compared to data from lice sampled on farmed salmon in the same regions. The resistant (R) allele was observed in salmon lice from wild salmon and sea trout throughout Norway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…During the last 30 years, salmon farming has increased the abundance of sea lice (Finstad & Bjørn, 2011;Fjørtoft et al, 2017;Thorstad & Finstad, 2018;Thorstad et al, 2015;Tully, Poole, Whelan, & Merigoux, 1993). During the last 30 years, salmon farming has increased the abundance of sea lice (Finstad & Bjørn, 2011;Fjørtoft et al, 2017;Thorstad & Finstad, 2018;Thorstad et al, 2015;Tully, Poole, Whelan, & Merigoux, 1993).…”
Section: Sea Licementioning
confidence: 99%
See 1 more Smart Citation
“…During the last 30 years, salmon farming has increased the abundance of sea lice (Finstad & Bjørn, 2011;Fjørtoft et al, 2017;Thorstad & Finstad, 2018;Thorstad et al, 2015;Tully, Poole, Whelan, & Merigoux, 1993). During the last 30 years, salmon farming has increased the abundance of sea lice (Finstad & Bjørn, 2011;Fjørtoft et al, 2017;Thorstad & Finstad, 2018;Thorstad et al, 2015;Tully, Poole, Whelan, & Merigoux, 1993).…”
Section: Sea Licementioning
confidence: 99%
“…The sea lice (Lepeophtheirus salmonis, Caligidae and Caligus elongatus, Caligidae) are natural parasites of sea trout that can propose major threats to trout in the marine environment. During the last 30 years, salmon farming has increased the abundance of sea lice (Finstad & Bjørn, 2011;Fjørtoft et al, 2017;Thorstad & Finstad, 2018;Thorstad et al, 2015;Tully, Poole, Whelan, & Merigoux, 1993). Sea lice induce ionoregulatory dysfunction, physiological stress, anaemia, reduced feeding and growth, changes in post-smolt behaviour, increased susceptibility to secondary infections, reduced disease resistance and ultimately mortality of individual sea trout (Finstad & Bjørn, 2011;ICES, 1997;Poole, Nolan, & Tully, 2000).…”
Section: Sea Licementioning
confidence: 99%
“…This competition over the natural habitat and food sources, as well as mates, may result in changes in the structure and productivity of the native stock (Fjørtoft et al 2017). In the case of escaped farmed salmon, it is reported that successful inbreeding between escaped farmed and native salmon reduces the fitness and productivity (McGinnity et al 2003), dilutes the genetic gene pools (Fjørtoft et al 2017;McGinnity et al 2004;Roberge et al 2008), and threatens the survival of the native salmon offspring (Hindar et al 2006). Karlsson et al (2016) found statistically significant introgression in half of the wild populations studied and levels of introgression above 10% in 27 of 109 rivers represented by adult samples.…”
Section: Escapementmentioning
confidence: 99%
“…Recent results suggest an extensive exchange of lice between farmed and wild hosts, indicating that in farming-dense regions in Norway, aquaculture represents a major driver of salmon louse population structure (Fjørtoft et al (2017). Furthermore, the annual loss of wild salmon to Norwegian rivers due to salmon lice was estimated at 50 000 adult salmon for the years 2010-2014.…”
Section: Sea Licementioning
confidence: 99%
“…High infection levels can cause the death of the host fish (Skilbrei, Bjørn, & Vollset, 2015;Vollset et al, 2017). Salmon farms are now the largest source of salmon lice found on wild salmon in Norway (Fjørtoft et al, 2017). This can reduce the number of fish returning to rivers to spawn (Krko sek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%